2023
DOI: 10.1007/s00203-023-03537-5
|View full text |Cite
|
Sign up to set email alerts
|

Biofertilizer effect of some zinc dissolving bacteria free and encapsulated on Zea mays growth

Abstract: Crop nutrition depends on zinc for enzymatic, oxidative, and metabolic processes. In the current study 20 different bacteria were isolated from five soil samples collected from different fields in Egypt. Bacterial isolates were screened for their ability to solubilize insoluble zinc oxide and zinc carbonate. The ability of selected isolates to tolerate soluble zinc was determined using different concentrations of (ZnSO4). Three bacterial isolates were selected with efficiency in solubilizing zinc oxide and zin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…The encapsulation protects the bacterial cells from contamination and the rice bran and gum Arabic which acts as a good carbohydrate source provides effective protection to the cells (He et al, 2015). Previous studies have also confirmed that the encapsulation of bacteria in alginate maintains the viability of biofertilizer for upto 3 months (Sultan et al, 2023). The biodegradation of beads is an important aspect in view of sustainability.…”
Section: Discussionmentioning
confidence: 92%
“…The encapsulation protects the bacterial cells from contamination and the rice bran and gum Arabic which acts as a good carbohydrate source provides effective protection to the cells (He et al, 2015). Previous studies have also confirmed that the encapsulation of bacteria in alginate maintains the viability of biofertilizer for upto 3 months (Sultan et al, 2023). The biodegradation of beads is an important aspect in view of sustainability.…”
Section: Discussionmentioning
confidence: 92%